A Facile yet Versatile Strategy to Construct Liquid Hybrid Energy‐Saving Windows for Strong Solar Modulation. Issue 10 (20th January 2023) - Li, Jichang; Gu, Pengyu; Pan, Hongyu; Qiao, Zhiyuan; Wang, Jianfeng; Cao, Yanxia; Wang, Wanjie; Yang, Yanyu
Abstract: Smart windows with light management and indoor solar heating modulation capacities are of paramount importance for building energy conservation. Thermochromic poly( N ‐isopropylacrylamide) (PNIPAm) hydrogel smart windows exhibit advantages of the relatively suitable transition temperature of 32 °C, high cost‐effective and automatic passive sunlight regulation, but sustain slow response rate and unsatisfactory solar modulation efficiency. Herein, a strategy of one‐step copolymerization of NIPAm and different olefine acids (OA) using reverse atom transfer radical polymerization method is developed to fabricate various chain/microparticle hybrids (CMH) for liquid energy‐saving windows. Synergetic mechanisms of thermal‐induced dissolution and aggregation of linear polymer chains integrated with water capture and release of microgel particles contribute to tunable light‐scattering behaviors and adaptive solar modulation. Without any post‐treatment, the as‐prepared poly( N ‐isopropylacrylamide‐ co ‐acrylic acid) (P(NIPAm‐ co ‐AA))‐based CMH suspension is injected into sandwich glass to construct energy‐saving windows, which exhibits appreciated near‐room‐temperature transition (26.7 °C), rapid response (5 s), extraordinary luminous transmittance (91.5%), and solar modulation efficiency (85.8%), resulting in a substantial decline of indoor temperature of 24.5 °C in simulation experiment. Combining the versatile strategy with flexible adjustment on transition temperature, multifarious P(NIPAm‐ co ‐OA)‐based CMH windows with eminent light management capacity are obtained. This work will powerfully promote the development and renovation of energy‐efficient windows. Abstract : Diversified liquid hybrid smart windows based on synergetic mechanisms of thermal‐induced dissolution and aggregation of linear chains and water capture and release of microgel particles are developed via facile copolymerization of N ‐isopropylacrylamide and various olefine acids. The windows possess easy large‐scale production, near‐room‐temperature transition, extraordinary light management, and indoor temperature regulation capacity, holding promises in commercial energy‐saving building materials.